Impact of Earthquake on Tourism Sector in Nepal - Rijal, Shiba Prasad (Tribhuvan University Journal, 2016)
This paper aims at highlighting the impacts of catastrophic Gorkha earthquake of April 25, 2015 on tourism sector of Nepal and is based on secondary data collected through literature narratives from published and unpublished sources. The 7.6 magnitude earthquake struck a large part of central Nepal and heavily affected the tourism business and livelihoods based on tourism. The overall economic loss due to the earthquake was equivalent to US$ 7 billion, and the disaster effect on tourism sector was estimated at 81241 million, 11.5 percent of total. Of the total amount, 76 percent represents the value of destroyed physical assets, and 24 percent reflects the losses and higher costs of production of goods and services arising from the disaster. The impact of earthquake was clearly observed on tourist arrival. The inbound tourist arrival was below pre-earthquake levels even after nine months of the earthquake, and fell to a six-year low in 2015. The impact of earthquake on economy and livelihoods was enormous. The overall economy was almost paralyzed for a long time. The recovery and the development of tourism business are closely tied with the reinstating of important tourism infrastructure and facilities.